Summary Record of Discussions of the National Development Council (NDC) Meetings Five Decades of Nation Building (Fifty NDC Meetings) Vol - I (1St To 14th Meeting) - Planning Commission (Planning Commission, 1952)
The Prime Minister welcomed the members to the first meeting of the National Development Council and observed that the National Development Council was essentially a forum for intimate cooperation between the State Governments and the Central Government for all the tasks of national development. It has been set up with three objects:- 1.to strengthen and mobilise the effort and resources of the nation in support of the Plan; 2.to promote common economic policies in all vital spheres, and 3.to ensure the balanced and rapid development of all parts of the country; Its functions would be 1.to review the working of the National Plan from time to time; 2.to consider important questions of social and economic policy affecting national development; and 3.to recommend measures for the achievement of the aims and targets set out in the National Plan.
Government of India Planning Commission
Government of India Planning Commission